NOTE-TAKING OF ENGLISH LESSONS AT TERTIARY LEVEL: A CONTEXT OF BANGLADESH - Islam, Farzana Sharmin Pamela (Universitas Negeri Makassar, 2017)
Note-taking is a common and an important classroom activity. Notes that students create in class while listening to the lectures given by lecturers, or while they review course material, become an important means of learning. It is a general perception of many learners and many of their instructors as well that note-taking is a common manifestation and intuitive skill to have, yet a few considers differently and encourage best practices for better performance. Unfortunately, many students are unaware of its benefits and so fail to appreciate that effective note-taking contributes to a great extent to their learning, and so the importance of cultivating their note-taking skills in course of their education period. This paper based on qualitative analysis provides an overview of how Bangladeshi students follow different strategies to take down notes in lecture sessions at tertiary level. The primary data for this paper has been collected from 35 students’ paragraph writing on a topic ‘How to take notes in a lecture’ in which the students were asked to reflect on their own note-taking strategies, how they get benefit from their notes, and their subsequent retrieval of information from the notes later on. The participants were from a ‘Basic English’ course as well as from English core courses at a highly rated private university in a metropolitan city in Bangladesh. This case study evolves around four aspects of note taking: firstly, the principal functions of note-taking; secondly, the main strategies students used for note-taking; thirdly, the benefits that the students derive through various approaches to note-taking; and lastly, the initiatives to improve the art of note taking as a successful tool in learning target subject matter. While some of the findings are in line with earlier studies, a few of them have their own uniqueness.